2001
DOI: 10.1159/000052658
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Speech Aerodynamics and Lateral Craniofacial Cephalometrics in Cleft Lip and Palate Patients with and without Finnish /r/-Sound Distortion

Abstract: To study the associations between the articulation of the Finnish /r/ sound and dentofacial and pharyngeal lateral cephalometric morphology and speech physiology, 18 (12 females, 6 males) young adult cleft patients’ /r/ sound was analysed auditorily by 3 speech experts. Laryngeal resistance (LARE), the smallest nasal cross-sectional area (NASA), nasal resistance (NASAR) and velopharyngeal orifice area (VEPA) were measured with pressure flow technique, and 31 points were identified from the lateral cephalograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…CL(A) boys with /r/ sound distortion seem to have slightly more anteriorly positioned hyoid bone. It is noteworthy that an anterior position of the hyoid bone has earlier been found to be significantly associated with /r/ sound disorders and low laryngeal resistance in adult CLP patients, who had in addition wider SNA angle [6], just like the present CP boys with /r/ sound distortions. The movements and function of the larynx is associated with the hyoid bone and mandible, and thus may be related to /r/ sound production.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…CL(A) boys with /r/ sound distortion seem to have slightly more anteriorly positioned hyoid bone. It is noteworthy that an anterior position of the hyoid bone has earlier been found to be significantly associated with /r/ sound disorders and low laryngeal resistance in adult CLP patients, who had in addition wider SNA angle [6], just like the present CP boys with /r/ sound distortions. The movements and function of the larynx is associated with the hyoid bone and mandible, and thus may be related to /r/ sound production.…”
Section: Discussionsupporting
confidence: 54%
“…The results, however, have been scattered and partly contradictory even though some isolated cephalometric measures have been attributed to misarticulations. The size and shape of the oral cavity, the relations of the tongue and palate and the position of the tongue and hyoid bone have been suggested to affect sound production [1][2][3][4][5][6]. Okazaki et al [7] found that narrowing and shortening of the anterior palate and its shallowness are associated with palatalized articulation, where sounds normally produced by the teeth or tooth ridge and tongue tip are produced instead by contact of the palate and the central portion of the tongue.…”
Section: Introductionmentioning
confidence: 99%